Tensiometer‐based irrigation scheduling and water use efficiency of field‐grown strawberries. (3rd May 2020) - Cormier, Julien; Depardieu, Claire; Letourneau, Guillaume; Boily, Carole; Gallichand, Jacques; Caron, Jean
Abstract: In recent decades, moisture‐based subsurface drip irrigation management strategies lead to water savings while maintaining strawberry yields in open fields. Most soils in the Québec City area are characterized by a high proportion of schist fragments and high hydraulic conductivity, causing substantial water losses following irrigation. Until now, little was known about the efficiency of soil‐moisture‐based irrigation strategies used on moderately coarse‐textured soils and their potential to improve water use efficiency (WUE). The first objective of this study was to test two tensiometer‐based irrigation managements for strawberry plants grown in a conventional system. Since field fumigation is increasingly restricted in field‐grown strawberries, we designed a raised‐bed trough system for use in the field and tested its productivity potential. The two irrigation methods included two treatments using pulsed irrigation: one with a constant irrigation threshold of −15 kPa (Pl), and the other with a variable threshold (−15/−30 kPa) adjusted daily to the predicted crop evapotranspiration (PlETc), in addition to a soilless treatment (SL) using a peat substrate and an irrigation threshold of −5 kPa. Compared to conventional irrigation, the PlETc treatment increased the WUE by 8 to 44% while maintaining marketable yields and fruit quality. Thus, this pulsed irrigation strategy is recommended for strawberry plants grown in clay loam soils. Strawberry plants grown in the soilless system gave 73 to 98% higher early marketable yield than soil cultivation. These results may encourage North American farmers to consider the soilless raised‐bed trough system as a viable alternative to conventional strawberry production systems.